(untitled) (AYUSHDHARA, 2018)
Expression of any disease is a chain of various processes starting from the encounter of etiological factors unto formation of that disease. In Ayurveda it is stated that Sharir Doshas i.e., Vata, Pitta and Kapha are accountable for all kind of functions in the body. At the same time if there is imbalance in these Doshas due to any reason, they can affect Dhatus (body tissues) and can cause various diseases. The causation of disease is attributed to Doshas hence it is essential to know the movement of these Doshas in our body at any given point of time. The word Kriyakala comprised of two words Kriya and Kala in which Kriya means treatment or action and Kala means time. Hence Kriyakala means the time of treatment or opportunities in the process of disease manifestation. Shat Kriyakala i.e. six stages are mentioned by Aacharya Sushruta which gives an idea regarding the present condition of Doshadushti and also the progress of disease in the body. It also guides us when to start treatment and what should be the line of treatment. In modern medicine it is described that one has to maintain homeostasis so as to remain in healthy. Human homeostasis refers to the body’s ability to physiologically regulate its inner environment to ensure its stability in response to fluctuations in the outside environment and weather. When body fails to maintain homeostasis it leads to pathogenesis and formation of disease. The pathogenesis of a disease is the biological mechanism (or mechanisms) that lead to the diseased state. The term can also describe the origin and development of the disease and whether it is acute, chronic, or recurrent. This article highlights correlation of the summery based on the Ayurvedic theory of Shatkriyakala with special reference to modern theory of homeostasis and pathogenesis.